The relationship between corporate takeovers and share prices for the target firms: Evidence for the indian stock market - Sehgal, Sanjay; Singh, Ashwani; Choudhary, Nitin (JABM, 2005)
The study examines the relationship between corporate takeovers and share prices for the Indian market using data for 31 target firms. We report significant extra normal profits for the pre-event period; this suggests that there are leakages in information which investors can exploit to make extra normal profits. On post-event basis, corporate takeovers seem to be good news for investors only if the object of offer is Change in Management. On the contrary, Change in Control and Substantial Acquisition cases seem to result in losses. There is no wealth creation of takeover targets classified on Consolidation of Holdings on ex-post basis. The study has important implications for investors and market regulators. It contributes towards the market efficiency literature for the Indian market